Task-Based Language Teaching Criteria in Textbook for Senior High School in Indonesia - Yuli Astriani; Rahmadi Nirwanto; Zaitun Qamariah (Jurnal Educatio FKIP UNMA, 2023)
The current study focused on activities and tasks that concluded in an English textbook used in a senior high school in Indonesia based on the TBLT's criteria. This study analyzed the content of an English textbook for senior high school grade X. The subject of this study was an English textbook titled "Pathway to English." The researchers used the qualitative descriptive method, especially in the analysis content, to analyze the tasks in the textbook. The researchers conducted this study in August 2022 at the library of IAIN Palangka Raya. The researchers utilized an observation instrument and an observation assessment form suggested by Akmal. Findings indicated that the textbook matched the standards for a good task based on Akmals' instruments. It showed that eight activities were classified as "strong" tasks, and seven obtained "weak" tasks. Moreover, this book also contains the four language skills with 12 activities of the book has more than one of the language skills in each activity and fulfills the criteria. In conclusion, this study indicates that the book is compatible with the Task-based Language Teaching (TBLT) criteria. However, the textbook mostly lacks the aspect of real-life activity and students' negotiation.